Advances in Resist Technology and Processing XX 2003
DOI: 10.1117/12.483761
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic understanding of post-etch roughness in 193-nm photoresists

Abstract: Surface roughness of 193 nm resists after a dry etch process is one of the critical issues in the implementation of 193 nm lithography to sub-100 nm technology nodes. Compared to commercial 248 nm resists, 193 nm photoresists exhibit significant roughness especially under the etch conditions for dielectrics, such as silicon dioxide and silicon nitride. While AFM analysis of DUV resists exhibit the mean roughness (R a ) of ~1 nm after blanket oxide etch, R a 's of 193 nm resists were found to be in the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…It is worth noting that the degree of surface roughening of 193 nm PR processed at 65 °C (Figure 3e) is comparable to that after argon plasma treatment with similar ion and VUV fluence, ∼3.5 nm 22. The severe roughening of p‐MAMA is also consistent with reports from plasma experiments 5, 15, 28. Moreover, VUV‐only or ion‐only exposures do not give the same degree of surface roughness.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It is worth noting that the degree of surface roughening of 193 nm PR processed at 65 °C (Figure 3e) is comparable to that after argon plasma treatment with similar ion and VUV fluence, ∼3.5 nm 22. The severe roughening of p‐MAMA is also consistent with reports from plasma experiments 5, 15, 28. Moreover, VUV‐only or ion‐only exposures do not give the same degree of surface roughness.…”
Section: Resultssupporting
confidence: 85%
“…While VUV photons can apparently play a role in both roughening and smoothing PRs, its synergism with other plasma‐generated species and the mechanisms associated with the resulting polymer texture are not well understood. Moreover, plasma experiments have shown that poly‐(2‐methyl‐2‐adamantyl methacrylate) (p‐MAMA), which is the leaving group in 193 nm PR, tends to roughen more compared to 193 nm PRs and associated model copolymers 5, 15, 28, 29. Surface roughening rate of adamantyl PR was correlated to deposited energy density during plasma processes 30.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the photoresist (PR) for a shorter wavelength has to be thinner and softer with respect to the dry etch process because the shorter wavelength has a higher opacity and a lower depth of focus. [6][7][8] With aggressive scaling of complementary metal oxide semiconductor (CMOS) technology, line width roughness (LWR) is increasingly becoming a larger component of the total variation because it does not scale down with device dimensions. 3,4 With increasingly scaling line width, the PR height has to be thinner to maintain the AR at an appropriate value 5 so that a successful patterning can be expected for sub-30 nm and beyond nodes.…”
Section: Introductionmentioning
confidence: 99%